2006
DOI: 10.1111/j.1460-9568.2006.04960.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐modal plasticity of the motor cortex while listening to a rehearsed musical piece

Abstract: Learning a musical piece requires the development of a strong linkage between sensory and motor representations. Audition plays a central role and a tight cortical auditory-motor corepresentation is a characteristic feature of music processing. Recent works have indicated the establishment of a functional connection between auditory and motor cortices during the learning of a novel piece, although no causal relation has yet been demonstrated. Here transcranial magnetic stimulation of the cortical motor represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 23 publications
7
120
0
5
Order By: Relevance
“…3B). These findings point to the heart of the action-listening mechanism and are in keeping with previous evidence for increased motor excitability (D'Ausilio et al, 2006) and premotor activity (Lotze et al, 2003;Bangert et al, 2006a) during listening to a rehearsed musical piece. Furthermore, our findings may be analogous to studies in the visuomotor domain, in which the mirror neuron system was involved only when the observed action was part of the observer's motor repertoire, such as in the case of dancers watching movements from their own dance style (but not from other styles) (Calvo-Merino et al, 2005) or in the case of humans watching biting actions (but not barking) (Buccino et al, 2004b).…”
Section: Discussionsupporting
confidence: 76%
“…3B). These findings point to the heart of the action-listening mechanism and are in keeping with previous evidence for increased motor excitability (D'Ausilio et al, 2006) and premotor activity (Lotze et al, 2003;Bangert et al, 2006a) during listening to a rehearsed musical piece. Furthermore, our findings may be analogous to studies in the visuomotor domain, in which the mirror neuron system was involved only when the observed action was part of the observer's motor repertoire, such as in the case of dancers watching movements from their own dance style (but not from other styles) (Calvo-Merino et al, 2005) or in the case of humans watching biting actions (but not barking) (Buccino et al, 2004b).…”
Section: Discussionsupporting
confidence: 76%
“…To test this hypothesis, TMS pulses were occasionally delivered over the right primary motor cortex to elicit motor evoked potentials (MEPs), which were recorded from a forearm muscle that would normally be used to play the left-hand part (cf. [92]). Differences in MEP amplitude suggested that distinct patterns of cortico-spinal excitability-inhibition and excitation-were associated with the representation of self and other, respectively (cf.…”
Section: (A) Representing Self and Other In The Brainmentioning
confidence: 99%
“…It was assumed that temporal predictions generated by the motor simulation process would facilitate rapid and accurate tempo adaptation. In order to manipulate the degree of motor simulation, the experimental design ensured that pianists either had or had not practiced the left-hand part prior to the tempo adaptation task [91,92]. Practicing the left-hand part was intended to assist the development of internal models that represented the sensorimotor transformations involved in performing it.…”
Section: (B) Neural Bases Of Real-time Coordination Skillsmentioning
confidence: 99%
“…The first experiment to investigate the influence of short term training on mirror system responses was carried out by D'Ausilio and colleagues [18]. Participants, who were all amateur pianists, were asked to learn the left hand part of a piece of piano music over a five day training period.…”
Section: Experience and Training Effects On Human Mirror Responsesmentioning
confidence: 99%